"Carta que un amigo escribe a otro": relación poética inédita de la dedicación de la iglesia jesuítica de San Pablo (Lima, 1638) - Cacho Casal, Rodrigo (El Colegio de México, 2016)
The library of the Hispanic Society of America holds a poetic manuscript –likely autograph– that contains an epistle written in octosyllabic form following the pattern of the ballad. The author, who disguises himself with the pseudonym of Menandro, gives an account to a friend of the celebrations and processions organised by the Society of Jesus for the dedication of the church of San Pablo in 1638. The Carta provides us with new information on this temple and the society of Lima at the time. This article offers an introduction and a critical edition of this unpublished text.